2018
DOI: 10.5597/00233
|View full text |Cite
|
Sign up to set email alerts
|

A review on the distribution, abundance, residency, survival and population structure of coastal bottlenose dolphins in Argentina

Abstract: Although bottlenose dolphins Tursiops truncatus are among the most common delphinid species, global population trends remain poorly understood. To improve the knowledge of the species in the Southwest Atlantic Ocean, thispaper reviews all available data related to the distribution and occurrence, abundance, residency and ranging patterns, group size and composition, survival and reproduction and population structure of the coastal bottlenose dolphin in Argentina. Most information proved to be scattered in time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…Presently, Lahille's Bottlenose Dolphins only occur in the southern part of the province of Buenos Aires, in Bahía Blanca and Bahía San Blas. Although no precise abundance estimates are available in this region specifically, the numbers are believed to be low based on photo-identification data for the time period 2010-2016, not exceeding 50 individuals (Vermeulen et al 2017). In the province of Río Negro, abundance was estimated at 83 (95% CI = 73 to 112) Lahille's Bottlenose Dolphins in Bahía San Antonio between 2009 and 2011 (using mark-recapture data and Pollock's Robust Design; Vermeulen and Bräger 2015), ranging at least along the entire coast of the San Matias Gulf (Failla et al 2016, Coscarella et al 2016.…”
Section: Argentina Subpopulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Presently, Lahille's Bottlenose Dolphins only occur in the southern part of the province of Buenos Aires, in Bahía Blanca and Bahía San Blas. Although no precise abundance estimates are available in this region specifically, the numbers are believed to be low based on photo-identification data for the time period 2010-2016, not exceeding 50 individuals (Vermeulen et al 2017). In the province of Río Negro, abundance was estimated at 83 (95% CI = 73 to 112) Lahille's Bottlenose Dolphins in Bahía San Antonio between 2009 and 2011 (using mark-recapture data and Pollock's Robust Design; Vermeulen and Bräger 2015), ranging at least along the entire coast of the San Matias Gulf (Failla et al 2016, Coscarella et al 2016.…”
Section: Argentina Subpopulationmentioning
confidence: 99%
“…Surveys conducted during the 1990s, failed to record any individuals in the same study area and it was concluded that these dolphins had completely disappeared in the past decade Rodriguez 2003, Vermeulen et al2017). No other coastal areas were identified where the abundance has increased substantially over time, dismissing any hypothesis of a distribution shift (Vermeulen et al 2017). Possible explanations for this disappearance relate to overfishing and other drastically increased anthropogenic pressures on the marine environment in that time period (e.g., pollution, habitat degradation, etc; Bastida and Rodriguez 2003), but no empirical data are available to sustain this hypothesis.…”
Section: Argentina Subpopulationmentioning
confidence: 99%
See 3 more Smart Citations